Kinetic photovoltage along semiconductor-water interfaces - Jidong Li (Nature Portfolio, 2021)
Common photovoltaic effect is across the interface of heterojunctions. Here, the authors find that scanning a light beam can induce a persistent in-plane photoelectric voltage along silicon-water interfaces, due to the following movement of a charge packet in the vicinity of the silicon surface.